Sheet-forming abiotic hetero foldamers - Baruah, Pranjal K.; Sreedevi, Naduthottiyil K.; Majumdar, Baisakhi; Pasricha, Renu; Poddar, Pankaj; Gonnade, Rajesh G.; Ravindranathan, Sapna; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
Abiotic hetero oligomers, adopting a well-defined extended self-assembled sheet-like structure, derived from conformationally constrained aliphatic and aromatic amino acid residues repeating at regular intervals are reported.

Structure determination and dynamics of protein-RNA complexes by NMR spectroscopy - Dominguez, Cyril; Schubert, Mario; Duss, Olivier; Ravindranathan, Sapna; Allain, Frederic H. T. (Progress in Nuclear Magnetic Resonance Spectroscopy, 2011)
Keywords: Dynamics; NMR spectroscopy; Protein-RNA complex; Structure determination

Silk fibroin-sophorolipid gelation: deciphering the underlying mechanism - Dubey, Parul; Kumar, Sugam; Aswal, Vinod K.; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Prabhune, Asmita; Nisal, Anuya (Biomacromolecules, 2016)
Silk fibroin (SF) protein, produced by silkworm Bombyx mori, is a promising biomaterial, while sophorolipid (SL) is an amphiphilic functional biosurfactant synthesized by nonpathogenic yeast Candida bombicola. SL is a mixture of two forms, acidic (ASL) and lactonic (LSL), which when added to SF results in accelerated gelation of silk fibroin. LSL is known to have multiple biological functionalities and hence hydrogels of these green molecules have promising applications in the biomedical sector. In this work, SANS, NMR, and rheology are employed to examine the assembling properties of individual and mixed SLs and their interactions with SF to understand the mechanism that leads to rapid gelation. SANS and NMR studies show that ASL assembles to form charged micelles, while LSL forms micellar assemblies and aggregates of a mass fractal nature. ASL and LSL together form larger mixed micelles, all of which interact differently with SF. It is shown that preferential binding of LSL to SF causes rapid unfolding of the SF chain leading to the formation of intermolecular beta sheets, which trigger fast gelation. Based on the observations, a mechanism for gelation of SF in the presence of different sophorolipids is proposed.

Silk fibroin-sodium dodecyl sulfate gelation: molecular, structural, and rheological insights - Hirlekar, Swarali; Ray, Debes; Aswal, Vinod K.; Prabhune, Asmita; Nisal, Anuya; Ravindranathan, Sapna (Langmuir, 2019)
A gelling agent is necessary to accelerate sol to gel transition in an aqueous solution of silk fibroin (SF), which otherwise takes several days to complete. In this paper, we investigate the mechanism of gelation of Bornbyx mori SF by a model anionic surfactant, sodium dodecyl sulfate (SOS). Even though interactions between SDS and proteins have been extensively investigated, most of these studies have focused on globular proteins, which undergo denaturation. The interaction with a fibrous protein such as SF is different and results in an altered secondary structure leading to gelation. In this work, the concentration-dependent gelation process of the SF-SDS system is examined using rheology, SANS, FTIR, and NMR. We observed preferential binding of SDS to specific regions on the SF chain, which aids structural changes favoring beta-sheet formation. We propose a mechanism for the accelerated sol-gel transition in the SF-SDS system.

Self-assembly of bispentadecylphenol substituted perylenediimide with PS-b-P4VP for structure-property insight into the core of core-shell micelles - Roy, Moumita; Rajamohanan, Pattuparambil R.; Ravindranathan, Sapna; Asha, S. K. (ACS Applied Polymer Materials, 2020)
We report the use of a ditopic molecular probe bispentadecylphenol substituted perylenediimide (PBI-PDP) to examine the molecular level self-assembly of polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) in tetrahydrofuran (THF). A series of complexes were prepared between PS-b-P4VP copolymers with varying lengths of the 4-vinylpyridine chain and PBI-PDP. Light scattering and NMR spectroscopic studies reveal that the self-assembled structures of the solid complexes are not fully disrupted when the complexes are dissolved in THF. NMR experimental parameters measured for the small probe molecule provide detailed insights into the structure of the assemblies in solution as well as the interaction between the small molecule and the block copolymer. Such insights can have important implications in manipulating the nanostructure of block copolymer micelles to suit various application requirements. The dynamics and distribution of the PBI-PDP molecules within the assemblies in solution show a dependence on the length of the P4VP block. Transmission electron microscopy was employed to study the evolution of morphologies in films prepared from the self-assembled structures in THF solutions.
Keywords: core corona interface; ditopic molecular probe; environment; micelles; perylenediimide; PS-b-P4VP; Self-assembly